2012
DOI: 10.1016/j.jmps.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Elasto-static micropolar behavior of a chiral auxetic lattice

Abstract: a b s t r a c tAuxetic materials expand when stretched, and shrink when compressed. This is the result of a negative Poisson's ratio n. Isotropic configurations with n % À1 have been designed and are expected to provide increased shear stiffness G. This assumes that Young's modulus and n can be engineered independently. In this article, a micropolarcontinuum model is employed to describe the behavior of a representative auxetic structural network, the chiral lattice, in an attempt to remove the indeterminacy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
171
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(179 citation statements)
references
References 37 publications
5
171
0
3
Order By: Relevance
“…In all of these cases, careful design of the microstructure has lead to effective Poisson's ratios ν < 0, despite the fact that the bulk materials are characterized by ν > 0. In particular, it has been shown that auxetic behavior can be achieved in a variety of highly porous materials [10], including foams with re-entrant [11][12][13][14][15] and chiral [16,17] microstructure, microporous polymeric materials [18], networks of rigid units [19] and skeletal structures [20]. Moreover, negative Poisson's ratio has also been shown in non-porous systems, such as laminates [21,22], sheets assemblies of carbon nanotubes [23], composites [24] and polycrystalline thin films [25].…”
mentioning
confidence: 99%
“…In all of these cases, careful design of the microstructure has lead to effective Poisson's ratios ν < 0, despite the fact that the bulk materials are characterized by ν > 0. In particular, it has been shown that auxetic behavior can be achieved in a variety of highly porous materials [10], including foams with re-entrant [11][12][13][14][15] and chiral [16,17] microstructure, microporous polymeric materials [18], networks of rigid units [19] and skeletal structures [20]. Moreover, negative Poisson's ratio has also been shown in non-porous systems, such as laminates [21,22], sheets assemblies of carbon nanotubes [23], composites [24] and polycrystalline thin films [25].…”
mentioning
confidence: 99%
“…Перемещения и вращения внутренних узлов трехзвенного соединения однозначно выражаются че-рез перемещения и вращения крайних узлов. Исключив внутренние степени свободы, после преобразований вы-ражение потенциала соединения может быть записано в виде (1). Выражения для параметров потенциала (1) че-рез параметры балочных элементов трехзвенного соеди-нения (рис.…”
Section: модель трехзвенного соединения балочного типаunclassified
“…Одним из примеров таких свойств является свойство ауксетичности, то есть свойство материала расширяться в поперечном направ-лении при его растяжении. Все более активно обсужда-ются вопросы моделирования, особенности поведения хиральных структур, возможности их практического применения [1][2][3]. Настоящая статья представляет обо-бщение известных результатов и некоторые новые ре-зультаты исследований авторов в этом направлении.…”
Section: Introductionunclassified
“…The mechanical behavior of chiral materials is of interest for the investigation of carbon nanotubes (Chandraseker and Mukherjee, 2006;Guz et al, 2007, Chandraseker et el., 2009, auxetic materials (Lakes, 1991(Lakes, , 1998Prall and Lakes, 1997;Spadoni and Ruzzene, 2012) and bones (Lakes et al, 1983;Park and Lakes, 1986). It is known that the deformation of chiral elastic materials cannot be described within classical elasticity.…”
Section: Introductionmentioning
confidence: 99%